Chlamydia Screening Among Women Aged 15 to 44 Years Who Reported Anal Sex During the Past 12 Months in the United States, 2013 to 2017. Issue 6 (24th June 2021) - Kumar, Sagar; Patel, Chirag G.; Tao, Guoyu
Abstract : There were 37.6% of women reporting anal sex who were tested for chlamydia. Those whose provider asked if they had vaginal/anal/oral sex were more likely to be tested than those whose provider did not. Abstract: Using the 2013–2017 National Survey of Family Growth, 37.6% of women with ≥1 anal sex partner in the last 12 months reported chlamydia testing at unspecified anatomic sites in the past 12 months. Women whose medical provider asked about type of sex (i.e., vaginal, oral, anal), compared with those whose provider did not, reported higher chlamydia testing.